Turisztikai mikro- és kisvállalkozások a magyarországi régiókban - Turcsányi, Katalin (Közép-Európai Közlemények, 2012)
Hungary has, from a touristic viewpoint, very favourable conditions (natural, cultural resources). Tourism might be one of the sectors, that can make Hungary competitive both in Europe and worldwide. To achieve this end, however, the existing problems need to be identified and solved. This research was conducted in the environment of small- and microbusinesses. The 214 questionnaires were distributed both in person and online in all the Hungarian touristic regions. Our inquiry extended to the economic environment of these businesses and also to their loan taking practices. We also looked at how well they know and utilize the tender opportunities in Hungary and the EU. Finally, we looked at how efficient they perceive the work of the advocate group different. These questions are important, among other things, because succesful tender applications and the developments that result from them may increase the international competitiveness of the Hungarian tourism industry.